2011
DOI: 10.1017/s002428291100003x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in stand structure due to the cessation of traditional land use in wooded meadows impoverish epiphytic lichen communities

Abstract: Wooded meadows with a history of traditional land use over thousands of years support a great diversity of various taxa. Today, however, high-species-rich communities in wooded meadows are threatened because of the cessation of traditional management in large areas. We studied lichen communities on 136 deciduous trees (Betula spp., Fraxinus excelsior and Quercus robur) in 12 wooded meadows in three regions of Estonia, and assessed the effect of habitat change due to the abandonment of traditional management on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 71 publications
2
27
0
2
Order By: Relevance
“…Similar results have been obtained by Bollinger et al (2007) in Switzerland, Leppik et al (2011) in Estonia and Ekman et al (2013) in Sweden, who found that crustose lichen species are related to trees with smooth bark, among which Fagus sylvatica is one of the host trees.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have been obtained by Bollinger et al (2007) in Switzerland, Leppik et al (2011) in Estonia and Ekman et al (2013) in Sweden, who found that crustose lichen species are related to trees with smooth bark, among which Fagus sylvatica is one of the host trees.…”
Section: Discussionsupporting
confidence: 87%
“…At the tree level, the bark morphology, diameter, competition with other epiphytes (Leppik et al 2011), bark pH (Mistry & Berardi 2005, Thor et al 2010) and aspect (Morley & Gibson 2010) are attributes which influence epiphytic lichen species.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lichens make up ecological groups based upon their shared requirements for a particular rhytidome texture. Leppik et al (2011) emphasized that the most probable causes of such differentiation among tree species are lichen Table 2. The values of Mann-Whitney U test for investigated natural reserves based on relative abundance of lichen species.…”
Section: The Influence Of Microhabitat Factors On Lichen Synusiae Fromentioning
confidence: 99%
“…Bark-pH was not found as discriminant parameter among the two tree species. On the contrary, many studies have demonstrated a strong epiphyte response to barkpH, explaining epiphyte community variation compared among tree species in both boreal and temperate systems (Hyvärinen et al 1992;Gauslaa 1995;Kuusinen 1996;Jüriado et al 2009;Lewis and Ellis 2010;Leppik et al 2011). Moreover, intraspecific studies, among boles of the same tree species, have indicated that barkpH/nutrient status may be modified by an interaction with the soil environment (Gauslaa 1995; Gustafsson and Eriksson 1995; Kermit and Gauslaa 2001) and with a subsequent effect on epiphyte community composition.…”
Section: Variability Of Lichen Diversity Across Scalesmentioning
confidence: 99%